A Review on Interactions between Exam Stress and Cognitive Processes - Roopali Sharma (AG Volumes, 2022)
In recent years, stress has become a worldwide issue that affects people of all ages and walks of life across the world. It’s a major issue that has an impact on their way of life. A fertile environment for the formation of stress is provided by academic life, which is characterised by the variety of stressors encountered by students at all levels of their education, as well as the variety of cognitive processes required to learn new information. Stress and its effects on learning and memory are discussed in this review. Cognitive processes such as learning and memory are essential for pupils’ success and growth. As a result of this, academic stress may have an impact on the three phases of learning and memory: encoding, consolidation and retrieval. These six models include functional near-infrared spectroscopy (fNIRS), electroencephalograms (EEGs), magnetic resonance imaging and electrocardiograms. The recommended literature evaluates the effects of academic stress on cognitive processes such as learning and memory using these techniques. Further research is suggested in light of these findings.